Zü’l-yedeyn hadisi : tahric ve tahlil - Uluman, Gülşah (My University, 2019)
Aralarında teâruz bulunduğu tespit edilen rivâyetler âlimler arasında ihtilâfa,insanlar arasında şüphe ve inkâra sebep olmaktadır. Zikredilen durum hadis ilmibünyesindeki problemlerin en önemlilerinden biri olarak dikkat çekmektedir. Buçalışmada, hakkında birçok ihtilâfın yer aldığı Zü’l-yedeyn hadisinin sened, bilhassametin açısından tenkit edilen yönlerine dair tespit ve değerlendirmeler bulunmaktadır.Hadisin Zührî tarikiyle nakledilen rivâyeti tartışmaların temelini oluşturmuştur.Metnindeki ifade farklılıkları âlimler arasında görüş ayrılığına neden olmuştur. Bunlararasında ilgili hâdiseyi Hz. Peygamber’e bildiren sahâbînin kimliği, sehiv hâdiseninmeydana geldiği namaz vakti, Zü’l-yedeyn hadisinin neshedildiği iddiaları, Hz.Peygamber’in yanılma sonrasında secde edip etmediği ve namazı tamamlamadankonuşmasının mâhiyeti gibi konular yer almaktadır. Böylece âlimler arasında ihtilâfçıkmasına sebep olan konular değerlendirilmiştir.

The narratives that seem contradictory to each other cause disputes among thescholars, lead people to having doubts about their faith, and it even gives a way toapostasy. This situation attracts attention as it is one of the most important problemswithin the body of the science of hadith. In this work, there are evaluations andassessments regarding the hadith known as Zhu’l-yadayn, about which there have beenlots of disagreements in terms of its chain of narrators and its text that has been open tocriticisms from some aspects. The basis of discussion roots in the narration which hadbeen transmitted by Zukhri. The dissimilarities in the expressions of the hadith’s texthave caused disagreements among the scholars. Among them, there are the matters ofthe identity of the companion of the Prophet who conveyed the incident to him, the timeof the prayer when the incident of sahiw took place, the claims about that the hadith ofZhu’l-yadayn has been abrogated, the case whether the Prophet prostrated after he madea mistake during prayer, the presence of his speaking before completing his prayer etc.Therefore, subjects that give a way to the emergence of disagreements among thescholars were evaluated.
Keywords: forgetting; Hadis; Hadith; Hırbâk; Hirbaq; Islam; İslam; makingmistake; sahiw; sehiv; unutma; yanılma; Zu’sh-shemaalayn; Zukhri; Zü’l-yedeyn; Zü’ş-şimâleyn; Zührî Zhu’l-yadayn